Kajian Penerapan Prinsip Mengenali Pengguna Jasa Bagi Notaris Dalam Mencegah Tindak Pidana Pencucian Uang Di Wilayah Daerah Istimewa Yogyakarta - Deddhy Herianto Sihotang; Rahma Ningtyas Saputri (Kajian Hukum, 2026)
The implementation of the Know Your Customer (KYC) principle constitutes a crucial instrument in the prevention and eradication of money laundering, particularly within the legal services sector involving the notarial profession. This study aims to analyze the level of understanding and the effectiveness of KYC implementation by notaries in preventing money laundering in the Special Region of Yogyakarta, with reference to Law Number 8 of 2010 and the Regulation of the Minister of Law and Human Rights Number 9 of 2017. This research employs a normative legal method, supported by statutory, conceptual, and limited empirical approaches through the examination of notarial practices. The findings indicate that the implementation of KYC by notaries has not been fully optimal, as reflected in limited understanding of their role as reporting parties and the existence of regulatory ambiguities, particularly regarding whether KYC should be applied to all clients or only to transactions exceeding a certain threshold. These conditions potentially undermine the effectiveness of anti-money laundering measures and increase the risk of notaries being inadvertently involved in illicit activities. Therefore, regulatory clarification and the enhancement of notaries’ capacity and awareness are necessary to ensure a more effective and comprehensive implementation of the KYC principle.